Engineering secure and dependable software systems - Pretschner, Alexander; Müller, Peter; Stöckle, Patrick (NATO science for peace and security series. Information and communication security ;, 2019)
Almost all technical systems currently either interface with or are themselves largely software systems. Software systems must not harm their environment, but are also often vulnerable to security attacks with potentially serious economic, political, and physical consequences, so a better understanding of security and safety and improving the quality of complex software systems are crucial challenges for the functioning of society. This book presents lectures from the 2018 Marktoberdorf summer school Engineering Secure and Dependable Software Systems, an Advanced Study Institute of the NATO Science for Peace and Security Programme. The lectures give an overview of the state of the art in the construction and analysis of safe and secure systems. Starting from the logical and semantic foundations that enable reasoning about classical software systems, they extend to the development and verification of cyber-physical systems, which combine computational and physical components and have become pervasive in aerospace, automotive, industry automation, and consumer appliances. Safety and security have traditionally been considered separate topics, but several lectures in this summer school emphasize their commonalities and present analysis and construction techniques that apply to both. The book will be of interest to all those working in the field of software systems, and cyber-physical systems in particular.